Crucial CD8(+) T-lymphocyte cytotoxic role in amphotericin B nanospheres efficacy against experimental visceral leishmaniasis. - Costa, LS (2014)
This work aims to develop poly(d,l-lactide-co-glycolide) (PLGA)-nanospheres containing amphotericin B (AmB) with suitable physicochemical properties and anti-parasitic activity for visceral leishmaniasis (VL) therapy. When compared with unloaded-PLGA-nanospheres, the AmB-loaded PLGA-nanospheres displayed an increased particle size without affecting the polydispersity and its negative surface charge. AmB stability in the PLGA-nanospheres was > 90% over 60-days at 30°C. The AmB-PLGA-nanospheres demonstrated significant in vitro and in vivo efficacy and preferential accumulation in the visceral organs. In addition, an immune-modulatory effect was observed in mice treated with AmB-PLGA-nanospheres, correlating with improved treatment efficacy. The in vitro cytotoxic response of the T-lymphocytes revealed that AmB-PLGA-nanospheres efficacy against VL infection was strictly due to the action of CD8 + - but not CD4 + -T lymphocytes. Overall, we demonstrate a crucial role for CD8 + cytotoxic T lymphocytes in the efficacy of AmB-PLGA nanospheres, which could represent a potent and affordable alternative for VL therapy. From the Clinical Editor: This study demonstrates a crucial role for CD8+ T lymphocytes in eliminating visceral leishmaniasis in a murine model by enhancing the cytotoxic efficacy of CD8+ T-cells via amphotericin-B-PLGA nanospheres, paving a way to a unique, potentially more potent and cost-effective therapeutic strategy.